Antibacterial effects of flavonoids and their structure-activity relationship study: a comparative interpretation - Shamsudin, Nur Farisya; Ahmed, Qamar Uddin; Mahmood, Syed; Shah, Syed Adnan Ali; Khatib, Alfi; Mukhtar, Sayeed; Alsharif, Meshari A.; Parveen, Humaira; Zakaria, Zainul Amiruddin (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
According to the latest report released by the World Health Organization, bacterial resistance to well-known and widely available antibacterial drugs has become a signiﬁcant and severe global health concern and a grim challenge to tackle in order to cure infections associated with multidrug-resistant pathogenic microorganisms efﬁciently. Consequently, various strategies have been orchestrated to cure the severe complications related to multidrug-resistant bacteria effectively. Some approaches involved the retardation of bioﬁlm formation and multidrug-resistance pumps in bacteria as well as the discovery of new antimicrobial agents demonstrating different mechanisms of action. In this regard, natural products namely alkaloids, terpenoids, steroids, anthraquinone, ﬂavonoids, saponins, tannins, etc., have been suggested to tackle the multidrug-resistant bacterial strains owing to their versatile pharmacological effects. Amongst these, ﬂavonoids, also known as polyphenolic compounds, have been widely evaluated for their antibacterial property due to their tendency to retard the growth of a wide range of pathogenic microorganisms, including multidrugresistant bacteria. The hydroxylation of C5, C7, C30, and C40; and geranylation or prenylation at C6 have been extensively studied to increase bacterial inhibition of ﬂavonoids. On the other hand, methoxylation at C30 and C5 has been reported to decrease ﬂavonoids’ antibacterial action. Hence, the latest information on the antibacterial activity of ﬂavonoids is summarized in this review, with particular attention to the structure–activity relationship of this broad class of natural compounds to discover safe and potent antibacterial agents as natural products.